Estudos de interação entre lectinas do tipo ConA e glicanos presentes na proteína Spike do novo Coronavírus - Correia, Sarah Elizabeth Gomes (2022)
Lectins are proteins with varied and wide applicability in the field of biotechnology. In general, they are defined as proteins that have the ability to bind specifically and reversibly to carbohydrates, without altering the structure of the ligand. the property of lectins of interactions through due failures, an application that results in relatively simple bioinformation and can generate large interactions with data. In this area of bioinformatics, the use of computer simulations in the study of lectins is promising for application in the health sphere, since it allows a quick and cheap prospection of potential ligands that may include those present in pathogens. Currently, the SARS-CoV-2 virus is one of the biggest threats to global health due to the high infection capacity, responsible for enormous pressure on the health sector due to a high number of infected with consequent hospitalizations. Studies that the infectious activity of coronaviruses is related to the activity of the spike glycoprotein in the envelope and that it has the ability to interact with the host cell 2 converting enzyme of the host. Therefore, the main objective of this study was to analyze the project of recognition of ConA-type lectins to the spike glycoprotein through molecular docking analysis with glycans present on the surface of this target molecule. In order for this objective library to be glycated, a process of building structures of three-dimensional steps, performed and embedded in the interaction, simulations of interaction between lectins and molecular docking assays to determine the most promising lectins in the interaction with a SARS S protein -CoV-2 that may proceed to experimental trials in the future.